Late start of upper secondary education and health-compromising behaviours among Finnish adolescents—a follow-up study - Henrik Dobewall; Leena Koivusilta; Sakari Karvonen; Pirjo Lindfors; Jaana M. Kinnunen; Mari-Pauliina Vainikainen; Arja Rimpelä (Oxford University Press, 2022)
Background
The Finnish government has emphasized the need to expedite educational transitions. We study if a late start of upper secondary education is related to health-related selection, namely health-compromising behaviours in adolescence.
Methods
A large cohort of adolescents from the seventh (12–13 years) and ninth (15–16 years) grades answered online classroom surveys (total n = 10 873). They were followed to the start of upper secondary education, obtained from the Joint Application Registry. We compared those who continued studies directly from the ninth grade with later starters. We measured late bedtime, breakfast not every school day, tooth brushing less than twice-a-day, monthly alcohol consumption, weekly smoking, daily energy drinks, physical activity <6 days/week and excessive screen time. Multilevel logistic regressions and latent class analyses were conducted.
Results
In gender and school adjusted models in the seventh grade, all behaviours except physical activity predicted the late start. The strongest predictor was smoking, OR = 2.96 (CI = 2.25–3.89). In the ninth grade, smoking, breakfast, tooth brushing and energy drinks, OR = 1.80, (CI = 1.36–2.39, strongest), were predictive. After controlling for sociodemographic background and academic achievement, associations for alcohol and screen time became non-significant in the seventh grade. In the ninth grade, only screen time remained significant, OR = 1.33 (CI = 1.04–1.71). Health-compromising behaviours formed clusters. Belonging to the unhealthy cluster predicted the late start in both grades, in adjusted models only in the seventh grade.
Conclusions
Students with health-compromising behaviours are less likely to start upper secondary education directly after the compulsory education. This may increase the risk for fragmentary educational trajectories and work careers.